Proactive marketing for the new and experienced library director : going beyond the gate count - Goldsmith, Melissa Ursula Dawn; Fonseca, Anthony J. (Chandos information professional series., 2014)
Academic libraries have continually looked for technological solutions to low circulation statistics, under-usage by students and faculty, and what is perceived as a crisis in relevance, seeing themselves in competition with Google and Wikipedia. Academic libraries, however, are as relevant as they have been historically, as their primary functions within their university missions have not changed, but merely evolved. Going beyond the Gate Count argues that the problem is not relevance, but marketing and articulation. This book offers theoretical reasoning and practical advice to directors on.